Probiotic and Its Fundamental Role In Gastrointestinal Health: A Literature Review - Fatridha Yansen (Faculty of Medicine, Universitas Andalas, 2024)
The gastrointestinal tracts are hosts to a wide variety of microorganisms known as intestinal microbiota. This gut microbiome may get disrupted that will influence the human health. Probiotics can restore the balance of gut microbiota by changing its composition and promoting its stability. Objective: This review aims to compile the role of probiotics in maintaining gastrointestinal health based on evidence-based through the modulation of the human gut microbiome. Method: This article is structured based on a literature review method by collecting and reviewing papers published in PubMed, Scopus, ScienceDirect, Springer, and Google Scholar. Results: The administration of probiotics have successfully shown evidenced beneficial health effects to prevent or treat for several main these several diseases including diarrhea, lactose intolerance and intestinal bowel diseases. Conclusion: Probiotics have been demonstrated to play key functions in the digestive system and to considerably reduce the symptoms of a variety of illnesses.